Bridging Data Discrepancies in Indonesia’s Self-Assessment System: Consultative Interventions at CV ABC - Astini, Yuli; Hardiningsih, Pancawati (Society : Jurnal Pengabdian Masyarakat, 2025)
This article analyzes the process of resolving Surat Permintaan Penjelasan Data dan/atau Keterangan (SP2DK) received by CV ABC, a food and beverage distributor, for the 2022 and 2023 tax years. In Indonesia's self-assessment tax system, discrepancies often arise between taxpayer reports and data held by tax authorities. To address these gaps and enhance compliance, the Directorate General of Taxes (DGT) issues SP2DK as a strategic supervisory instrument. This study utilized a qualitative case study approach with a consultative assistance method (pendampingan). The analysis was conducted through data equalization and a thorough review of relevant tax regulations. The findings revealed common issues such as an unusually low profit margin, unreported bonus income in the form of goods, and data inconsistencies in Income Tax Article 23 and Value added tax return. Most findings were successfully resolved through clarification and voluntary corrections by the taxpayer. This case highlights the critical importance of professional assistance and strong internal controls to improve tax compliance and overcome administrative complexities, particularly for micro, small, and medium-sized enterprises (MSMEs). The findings of this study are expected to provide practical insights for other taxpayers and serve as a valuable reference for academics and policymakers